2020
DOI: 10.3389/fmicb.2020.00825
|View full text |Cite
|
Sign up to set email alerts
|

Cholera Toxin Production in Vibrio cholerae O1 El Tor Biotype Strains in Single-Phase Culture

Abstract: Vibrio cholerae O1 serogroup strains have been classified into classical and El Tor biotypes. Cholera, a life-threatening diarrheal disease, can be caused by either biotype through the cholera toxin (CT) that they produce. To increase our knowledge of the pathogenicity of bacteria, we must understand the toxigenicity of bacteria. CT production by classical biotype strains in simple single-phase cell cultures has been established; however, special culture media and growth conditions that are not appropriate for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 36 publications
(44 reference statements)
3
21
0
Order By: Relevance
“…This study utilised the cell free culture filtrate of O1 El Tor Ogawa V. cholerae isolated from clinical samples during the cholera out-breaks in Karnataka, India [ 15 , 16 ] for both in vitro as well as in vivo studies. It has been well reported that O1 El Tor Ogawa strain of V. cholerae produce Cholera toxin [ 17 ], non-membrane damaging cytotoxin [ 18 ] into culture supernatant along with other toxins such as Accessory Cholera toxin [ 19 ], Zonula occludens toxin [ 20 ], Multifunction auto processing repeats-in-toxin [ 21 ], Haemolysin [ 22 ] which are responsible for the pathogenesis of V. cholerae . Previous research has shown that the bacterium efficiently secretes both CT and NMDCY in AK1 media [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study utilised the cell free culture filtrate of O1 El Tor Ogawa V. cholerae isolated from clinical samples during the cholera out-breaks in Karnataka, India [ 15 , 16 ] for both in vitro as well as in vivo studies. It has been well reported that O1 El Tor Ogawa strain of V. cholerae produce Cholera toxin [ 17 ], non-membrane damaging cytotoxin [ 18 ] into culture supernatant along with other toxins such as Accessory Cholera toxin [ 19 ], Zonula occludens toxin [ 20 ], Multifunction auto processing repeats-in-toxin [ 21 ], Haemolysin [ 22 ] which are responsible for the pathogenesis of V. cholerae . Previous research has shown that the bacterium efficiently secretes both CT and NMDCY in AK1 media [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…TcpA expression in V. cholerae strains was examined in various culture media (LB, LB Tris-Cl pH 6.5, PBS-buffered LB, and AKI media) at 30°C or 37°C as described [ 37 ]. The optimal culture conditions for expression of TcpA for the bacterial strains were determined as follows; E. coli DH5α, V. cholerae O395, YJB001 (O395- toxT -139F), EJK003 (Cairo48- toxT -139F), JHB001 (Cairo48- toxT -139F- tcpA -ET), EJK005 (Phil6973- toxT -139F), EJK006 (4260B- toxT -139F), 569B, and EJK007 (569B- toxT -139F) have been cultured in LB media at 30°C.…”
Section: Methodsmentioning
confidence: 99%
“…pCVD442- toxT -139F was conjugally transferred to strains O395, N16961, T19479, EJK001 (IB5230-ch1-kan), Cairo48, Cairo50, Phil6973, 4260B, and 569B to replace their toxT -139Y allele with toxT -139F. The replacement of the toxT allele in each strain was confirmed by sequencing [ 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Health Organization estimated that cholera infects 1 to 4 million people and claims up to 143,000 lives each year (31). Cholera toxin and toxin-coregulated pilus are two major virulence factors produced by epidemic V. cholerae strains of serotypes O1 and O139 (2). Nevertheless, some non-O1/ O139 strains that do not produce cholera toxin and toxincoregulated pilus have been reported to cause sporadic diarrhea and gastroenteritis in humans, indicating that other virulence factors exist (33).…”
mentioning
confidence: 99%